Persistence of endocrine-disrupting chemicals in agricultural soils. Issue 3 (1st May 2006) - Lorenzen, Angela; Burnison, Kent; Servos, Mark; Topp, Edward
Abstract : Biosolids and animal wastes can contain natural hormones or synthetic chemicals that have the potential to disrupt endocrine function in wildlife should they move offsite. The persistence in soil of estrogenic substances that could reach agricultural land via fertilization with organic amendments has been evaluated. 4-Nonylphenol, ethynylestradiol, estradiol, and estrone are rapidly dissipated in soils under a range of conditions typical of a temperate growing season with half-lives ranging from a few hours to a few days. We conclude that these chemicals are rapidly removed from aerated soils under temperate growing conditions such that application methods that minimize preferential flow or runoff of animal or human wastes should protect adjacent water from contamination. The use of recombinant yeast and cell culture estrogen receptor gene transcription bioassays were investigated as potential tools to detect non-labile estrogenic or anti-estrogenic substances in runoff from soils receiving liquid swine slurry or biosolids. Key words : biosolids, manures, endocrine disruption, estrogen, nonylphenol, soil persistence, bioassay.